Fluid velocity measurement by processing images of neutrally-buoyant, phosphorescent tracer particles - McCay, JoAnn Margaret, 1962- (The University of Arizona., 1987)
A technique for measuring fluid velocities by means of neutrally-buoyant, phophorescent particles was investigated in a small-scale water jet facility. A nitrogen laser briefly illuminated the flow, exciting only those particles resident within the pulsed beam. The particles luminesce for a short while following excitation, during which time they also move with the flow. This creates a visible particle streak, the intensity of which decays along the direction of motion. A strobe illuminates the particles again a known time following the laser pulse. The magnitude and direction of a particle's velocity in the plane of view are deduced from an image of it streak captured by a video camera and recorded by a digital image processing system.